Conservation tillage, local organic resources and nitrogen fertilizer combinations affect maize productivity, soil structure and nutrient balances in semi-arid Kenya - Kihara, J.; Bationo, A.; Mugendi, Daniel N.; Martius, C.; Vlek, P.L. (Springer, 2011)
Smallholder land productivity in drylands can be increased by optimizing locally available resources, through nutrient enhancement and water conservation. In this study, we investigated the effect of tillage system, organic resource and chemical nitrogen fertilizer application on maize productivity in a sandy soil in eastern Kenya over four seasons. The objectives were to (1) determine effects of different tillage-organic resource combinations on soil structure and crop yield, (2) determine optimum organic–inorganic nutrient combinations for arid and semi-arid environments in Kenya and, (3) assess partial nutrient budgets of different soil, water and nutrient management practices using nutrient inflows and outflows. This experiment, initiated in the short rainy season of 2005, was a split plot design with 7 treatments involving combinations of tillage (tied-ridges, conventional tillage and no-till) and organic resource (1 t ha−1 manure + 1 t ha−1 crop residue and; 2 t ha−1 of manure (no crop residue) in the main plots. Chemical nitrogen fertilizer at 0 and 60 kg N ha−1 was used in sub-plots. Although average yield in no-till was by 30–65% lower than in conventional and tied-ridges during the initial two seasons, it achieved 7–40% higher yields than these tillage systems by season four. Combined application of 1 t ha−1 of crop residue and 1 t ha−1 of manure increased maize yield over sole application of manure at 2 t ha−1 by between 17 and 51% depending on the tillage system, for treatments without inorganic N fertilizer. Cumulative nutrients in harvested maize in the four seasons ranged from 77 to 196 kg N ha−1, 12 to 27 kg P ha−1 and 102 to 191 kg K ha−1, representing 23 and 62% of applied N in treatments with and without mineral fertilizer N respectively, 10% of applied P and 35% of applied K. Chemical nitrogen fertilizer application increased maize yields by 17–94%; the increases were significant in the first 3 seasons (P < 0.05). Tillage had significant effect on soil macro- (>2 mm) and micro-aggregates fractions (<250 μm >53 μm: P < 0.05), with aggregation indices following the order no-till > tied-ridges > conventional tillage. Also, combining crop residue and manure increased large macro-aggregates by 1.4–4.0 g 100 g−1 soil above manure only treatments. We conclude that even with modest organic resource application, and depending on the number of seasons of use, conservation tillage systems such as tied-ridges and no-till can be effective in improving crop yield, nutrient uptake and soil structure and that farmers are better off applying 1 t ha−1 each of crop residue and manure rather than sole manure.
DOI : 10.1007/s10705-011-9423-7
Keywords: Crop residue; Manure; Soil aggregation; Nutrient balance; Tillage